Trends and comparative analysis of the burden of migraine in China and globally from 1990 to 2021: an analysis based on the 2021 global burden of disease study - Peng, Bo; Tu, Yuluo; Hu, Suifa; Xie, Gui (Frontiers in Neurology, 2025)
BackgroundMigraine is a common neurological disorder that has become an increasingly significant public health issue. This study aims to analyze the burden of migraine in China and globally from 1990 to 2021, exploring epidemiological trends and differences, thus providing scientific evidence for migraine prevention and control.MethodsBased on the 2021 Global Burden of Disease (GBD) study, we assessed migraine burden in China and globally from 1990 to 2021 using indicators including incidence, prevalence, disability-adjusted life years (DALYs), and age-standardized rates. The epidemiological trends were analyzed by calculating the estimated annual percentage change (EAPC). Health inequality analysis was conducted to explore the association between migraine burden and the sociodemographic index (SDI). Decomposition analysis quantified contributions of age structure, population growth, and epidemiological changes to migraine burden. Additionally, the Bayesian Age-Period-Cohort (BAPC) model was applied to predict migraine burden in China and globally over the next 10 years.ResultsCompared with 1990, the number of migraine cases, prevalence, and DALYs in both China and globally significantly increased by 2021, though the global growth rate was considerably higher. Between 1990 and 2021, China experienced greater increases in age-standardized incidence rates (ASIR), age-standardized prevalence rates (ASPR), and age-standardized DALYs rates (ASDR) than the global average. Migraine burden was predominantly concentrated among adolescents and young adults, and females consistently exhibited a higher burden than males. Health inequality analysis revealed increasing disparity across 204 countries and regions, with a concentrated migraine burden in high socio-demographic index (SDI) countries, positively correlated with SDI. Decomposition analysis indicated that population growth was the primary driver of migraine burden changes in both China and globally. BAPC modeling predicted that the age-standardized incidence, prevalence, and DALY rates for migraine will continue to rise in China, whereas these rates are expected to slightly decline globally.ConclusionsMigraine burden is rising in both China and globally, driven by multiple factors such as age, gender, population growth, and SDI. There is an urgent need for precise interventions to reduce migraine's public health impact.